AKTIVITAS HARIAN ELANG BRONTOK (Nisaetus cirrhatus) DI PUSAT KONSERVASI ELANG KAMOJANG - Safanah, Nabila Ghitha; Partasasmita, Ruhyat; Rakhman, Zaini (Metamorfosa: Journal of Biological Sciences; Vol 5 No 1 (2018), 2018)
The role of changeable hawk-eagle ( Nisaetus cirrhatus ) in nature is a predator that controls the ecosystem. This eagle is one of the species of predators whose existence is threatened by deforestation, human disturbance, and illegal hunting, which could lead to a decrease in the number of species in nature. Captured changeable hawk-eagle could result in a change of natural behavior when they are placed in a cage. For the recovery of these behavior, changeable hawk-eagles need to be rehabilitated so that the eagles can be reintroduce back to the nature. This purpose of this study is to understand the daily activities of changeable hawk-eagle during rehabilitation period. This study was conducted in Kamojang Eagle Conservation Center (PKEK), Garut West Java. The method used in this study is observation of the field using ad-libitum method. All activities are recorded during eagle observation in a cage. The observation is done every three days each week for five weeks. The observed activities are resting, moving, eating, and others. The results revealed that resting is an activity with the largest proportion of time with 74%, whereas other activities with 4% such as moving the tail, pecking the perch and prey hunting are activities that have the smallest time proportion in the rehabilitation period.